Bahaya Eksploitasi terhadap Masa Depan Anak - Windi Juwita Sari (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2024)
Child exploitation is a serious problem that affects the future of the nation's next generation. Even though the Child Protection Law Number 23 of 2002 regulates the prohibition of child exploitation, various forms of exploitation such as economic, social and sexual exploitation are still widespread in Indonesia. Based on data from the Indonesian Child Protection Commission (KPAI), cases of child exploitation have increased significantly from year to year. Exploited children often work in inappropriate conditions, such as being "silvermen" for busking or begging, which affects their physical, psychological and social conditions. This research aims to explore the impact of exploitation on children as a whole, especially in terms of physical health, psychological development and educational opportunities. Apart from that, economic factors which are the main triggers for exploitation are also discussed as the root of the problem. The long-term impacts of child exploitation, such as trauma, low educational opportunities, and limited access to escape the cycle of poverty, are the main concerns in this paper. It is hoped that this research will provide a deeper understanding of the urgency of protecting children from exploitation and the importance of collective efforts in breaking the cycle of exploitation for a better future for children.